2013
DOI: 10.3354/esr00556
|View full text |Cite
|
Sign up to set email alerts
|

Living together in the night: abundance and habitat use of sympatric and allopatric populations of slow lorises and tarsiers

Abstract: Throughout much of Asia, slow lorises (Nycticebus) and tarsiers (Tarsius) live allopatrically, but on several islands, including Sumatra and Borneo, they occur in sympatry. Dwindling habitats could result in resource competition within these sympatric populations, as the diets of these species overlap. To assess the possibility of resource competition, we gathered data from the literature on the abundance and microhabitat structure of slow loris and tarsier species throughout their ranges. We also estimated ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Their average height is habitat-dependent, but all lorises use all heights available, including the highest canopy and the ground if there is no other choice., However, they most commonly are observed below 10 m. The only exception may be the slow lorises from Borneo; it seems that sharing the forest with tarsiers keeps slow lorises at higher forest levels due to interspecific competition. 35 No loris moves as little as 15-20 m per night; Loris typically moves approximately 1 km per night, whereas Nycticebus typically moves more than 5 k m more than most bushbabies do, equalling the ranges of much larger primates such as gibbons. 36 Lorises certainly do not live in one tree; rather, they range widely, with a complex system of range overlap.…”
Section: Lorisinaementioning
confidence: 99%
“…Their average height is habitat-dependent, but all lorises use all heights available, including the highest canopy and the ground if there is no other choice., However, they most commonly are observed below 10 m. The only exception may be the slow lorises from Borneo; it seems that sharing the forest with tarsiers keeps slow lorises at higher forest levels due to interspecific competition. 35 No loris moves as little as 15-20 m per night; Loris typically moves approximately 1 km per night, whereas Nycticebus typically moves more than 5 k m more than most bushbabies do, equalling the ranges of much larger primates such as gibbons. 36 Lorises certainly do not live in one tree; rather, they range widely, with a complex system of range overlap.…”
Section: Lorisinaementioning
confidence: 99%
“…Most of the species of nocturnal primates with which P. edwardsi is sympatric, Allen's squirrel galago Sciurocheirus alleni (Waterhouse, 1838), A. calabarensis and Demidoff's dwarf galago Galagoides demidovii (G. Fischer, 1808) typically occupy the lower strata and highly connected undergrowth of the forest (Charles-Dominique, 1974;Oates, 2011). Munds et al (2013) found that slow lorises occupy higher levels when they are sympatric with tarsiers Cephalopachus spp. Bersacola et al (2015) also found evidence of niche partitioning where P. edwardsi is sympatric with large-eared greater galago Otolemur crassicaudatus É. Geoffroy, 1812 in Angola.…”
Section: Discussionmentioning
confidence: 97%
“…Slow lorises ( Nycticebus spp.) are nocturnal arboreal primates distributed throughout Southeast Asia, from northeastern India and southern China to the Thai-Malay Peninsula and extending further south to the islands of Sumatra, Java and Borneo (Nekaris et al, 2008; Munds et al, 2013). Based on morphological similarities among different lorisiform primates coupled with their nocturnal lifestyle, lorises are regarded as cryptic primates that are difficult to detect moving throughout the forest (Nekaris and Bearder, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Based on morphological similarities among different lorisiform primates coupled with their nocturnal lifestyle, lorises are regarded as cryptic primates that are difficult to detect moving throughout the forest (Nekaris and Bearder, 2007). From the eight currently recognized species (Groves, 1998; Ravosa, 1998; Chen et al, 2006; Munds et al, 2013; Pozzi et al, 2014, 2015), only the Philippine slow loris ( N. menagensis ) has been recorded inhabiting the Lower Kinabatangan Wildlife Sanctuary in Sabah, Malaysian Borneo (Munds et al, 2013).…”
Section: Methodsmentioning
confidence: 99%